The "female quota" in the province of Cordoba. Implications and Scope - Di Rienzo, Gloria (Centro de Estudios Avanzados, 2016)
Law 8901/2000 established "the principle of equivalent gender participation" in electoral processes in the province of Córdoba.  In this work, the effectiveness of the norm was analyzed and measured as part of the dynamics of the exercise of political rights of the largest sector that constitutes Cordoba's citizenship: women. It was based on two levels of analysis: the legal body, its scope and contexts of production, and social impact, i.e. the implementation of established rights; the electoral processes carried out between 2000 and 2007 inclusive were compared with the legislative election carried out prior to 2000, using the parameters indicated; it was found that the female quota in the legislature maintained 30 per cent. It is concluded that the current law that contemplates "the principle of gender-equivalent participation", which was presented as superseding its homologues, did not produce the expected improvements in its implementation.